The Hydrochidae (Coleoptera) of Morocco with a redescription of Hydrochus cf. obtusicollis Fairmaire, 1877 - Benamar, Loubna; Bennas, Nard; Henegouwen, Arno Van Berge; García-Meseguer, Antonio José; Hassoun, Mustapha; Benali, Naouar; Millán, Andrés (Zootaxa, 2024)
A checklist of water beetles of the family Hydrochidae from Morocco is presented. The study compiles data gathered from a deep literature review and field surveys at 397 freshwater localities between 1985 and 2023. The checklist also contains information concerning type localities and detailed distributions for the eight species found. We include a detailed redescription of Hydrochus cf. obtusicollis Fairmaire, 1877, currently listed as a synonym of H. flavipennis Küster, 1852, but clearly representing a different species. In addition, a key, based largely on male genitalia, is presented for Moroccan species. This work is the first detailed study of the family Hydrochidae in Morocco, which can provide a basis for future progress in the knowledge of Moroccan aquatic Coleoptera, an insect group of great ecological interest.